“Contaminator y Acuatichic”: characters who challenge university integrality in psychology. Challenges of comprehensive higher education in rural settings (Cuadernos de Extensión Universitaria de la UNLPam, 2024)
In 2018, representatives of the Popular Assembly for Water of Luján de Cuyo de Mendoza shared their concern about possible effects on the health of people belonging to the town of El Remanso, located in a territory close to oil exploitation . Upon reaching the community we recognized various ways in which ongoing economic activities affected the common goods that modified ways of life. From the Community Mental Health subject of the psychology degree at the University of Mendoza, work has been done on the construction of comprehensive higher education spaces to carry out interdisciplinary and intersectoral approaches in place. These resulted in the carrying out of critical epidemiological investigations and participatory community interventions, including a play with childhoods. This article offers a reflection on the possibilities offered by territorial work in its different modalities. We recover field diaries, research reports and professional practices to reconstruct the contributions of comprehensive training methodology. The experience generated questions in students of professional practices, in neighbors and allowed modifications in the subject program to adapt it to the territorial particularities.
Keywords: comprehensive training in higher education; water pollution; community participation; rurality